2002
DOI: 10.1046/j.1365-2893.2002.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic‐tree analysis elucidating nosocomial transmission of hepatitis C virus in a haemodialysis unit

Abstract: Nosocomial transmission of hepatitis C virus (HCV) subtype 1b involving 11 haemodialysis patients occurred in a haemodialysis unit in Japan in March 2000. Sequencing of the HCV-E1 region (411-bp) and phylogenetic-tree analysis showed near identity between HCV isolates derived from these patients and a haemodialysis patient who was known to be HCV-positive. The mode of transmission could not be conclusively established, but retrospective analysis suggested that the sharing of contaminated multidose vials of hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 24 publications
1
27
0
1
Order By: Relevance
“…Sequencing the HVR-1 region of the E2 gene demonstrated that the de novo infection was established from one of the strains present in HCVinfected patients in the same center in all but one case. This is in accordance with other studies conducted in hemodialysis centers with epidemic HCV infections where sequencing relevant regions, such as HVR-1 of E2 or NS5B, indicated the source of infections [Allander et al, 1994;Stuyver et al, 1996;Le Pogam et al, 1998;Izopet et al, 1999;Katsoulidou et al, 1999;Grethe et al, 2000;Halfon et al, 2002;Kokubo et al, 2002].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Sequencing the HVR-1 region of the E2 gene demonstrated that the de novo infection was established from one of the strains present in HCVinfected patients in the same center in all but one case. This is in accordance with other studies conducted in hemodialysis centers with epidemic HCV infections where sequencing relevant regions, such as HVR-1 of E2 or NS5B, indicated the source of infections [Allander et al, 1994;Stuyver et al, 1996;Le Pogam et al, 1998;Izopet et al, 1999;Katsoulidou et al, 1999;Grethe et al, 2000;Halfon et al, 2002;Kokubo et al, 2002].…”
Section: Discussionsupporting
confidence: 92%
“…Nosocomial transmission of HCV infection has become the main source of infection in chronic hemodialysis patients rather than transmission by blood-derived products. Molecular phylogenetic analyses have shown that many outbreaks of HCV infection are not linked to the transfusion of packed red blood cells or blood products [Allander et al, 1994;Stuyver et al, 1996;Le Pogam et al, 1998;Izopet et al, 1999;Katsoulidou et al, 1999;Grethe et al, 2000;Halfon et al, 2002;Kokubo et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the genotyping of HCV isolates is a useful tool in molecular studies carried out to establish the source of outbreaks in hemodialysis centers and other nosocomial settings (4,5).…”
mentioning
confidence: 99%
“…Transmission from an infected patient to another patient being treated simultaneously in the same room has emerged as the main mechanism of HCV transmission among patients, treated by hemodialysis [Katsoulidou et al, 1999;Kokubo et al, 2002]. The frequent percutaneous procedures provide many opportunities for contamination of surfaces and instruments with small amounts of HCV-infected blood.…”
Section: Discussionmentioning
confidence: 99%